EKSTRAKURIKULER DRUMBAND DI SMA NEGERI 1 PADANG GANTING - Defrianti Defrianti; Syahrel Syahrel; Yos Sudarman (SENDRATASIK UNP, 2017)
The purpose of this study is to describe the implementation of extracurricular drumband in SMA Negeri 1 Padang Ganting. The research method used qualitative research type with descriptive-analysis approach. Technique of collecting research data with observation, interview, and literature study. While data analysis is done by collecting primary data and secondary data. The result of the research shows that the implementation of the drumband extracurricular in SMA Negeri 1 Padang Ganting is in various problems, especially from the less trainer side, the boring material, the undisciplined students, the limited facilities, and no estuary of the drumband activities that cause students, And the drumband organization SMA Negeri 1 Padang Ganting can perform again. Keywords: Extracurricular Drumband